2008
DOI: 10.1099/mic.0.2007/014944-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of soluble secreted proteins from appressoria of Colletotrichum higginsianum by analysis of expressed sequence tags

Abstract: The hemibiotrophic ascomycete Colletotrichum higginsianum causes anthracnose disease on brassica crops and the model plant Arabidopsis. Melanized appressoria pierce the host cuticle and cell wall to form specialized biotrophic hyphae inside living epidermal cells. To identify proteins secreted by appressoria that may function as virulence effectors, a cDNA library was prepared from mature appressoria formed in vitro. Bidirectional sequencing of 980 clones generated 1442 high-quality expressed sequence tags (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 70 publications
1
53
0
Order By: Relevance
“…ChEC6:mRFP and ChEC36:mRFP fusions were expressed and targeted to this pore before any ingression into the host cell had occurred. Given that in vitro and in planta appressoria are morphologically indistinguishable [29] and that these effectors were not expressed by in vitro appressoria, this suggests that host-derived signals, rather than developmental cues, induce ChEC expression. Moreover, these signals must be sensed before penetration hyphae emerge, presumably via the wall-less pore region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ChEC6:mRFP and ChEC36:mRFP fusions were expressed and targeted to this pore before any ingression into the host cell had occurred. Given that in vitro and in planta appressoria are morphologically indistinguishable [29] and that these effectors were not expressed by in vitro appressoria, this suggests that host-derived signals, rather than developmental cues, induce ChEC expression. Moreover, these signals must be sensed before penetration hyphae emerge, presumably via the wall-less pore region.…”
Section: Discussionmentioning
confidence: 99%
“…(c). A control gene encoding a non-secreted calpain protease, although absent from most sequenced ascomycete genomes [29], is conserved in all species tested. The ethidium bromide-stained agarose gel before blotting is shown below as loading control.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Studies conducted to date have investigated the secretome at different stages of the infection process, including penetration (appressorial morphogenesis), biotrophic and necrotrophic stages. Kleeman et al [13] identified 26 putative soluble secretory proteins from a cDNA library prepared from mature appressoria of C. higginsianum grown in vitro . Sixteen candidate effector proteins were discovered from Venturia inaequalis , the causal agent of apple scab, on the basis of their small size (< 400 amino acids in length when mature), presence of cysteine residues and of a putative SP [14].…”
Section: Introductionmentioning
confidence: 99%
“…Biocomputational algorithms are used to scan Nterminal signal peptides in predicted proteins from whole-genome sequences or expressed sequence tags (ESTs). Using this approach, dozens of secreted proteins were identified from P. infestans (Torto et al 2003;Tian et al 2004), Colletotrichum higginsianum (Kleemann et al 2008), and Venturia inaequalis (Brown et al 2009). The signal sequence trap is a yeast-based genetic screen for signal peptide encoding cDNA.…”
Section: Secretomementioning
confidence: 99%